Quality of urban space as a factor of Almaty’s sustainable economic development - N. K. Nurlanova; F. G. Alzhanova; Z. T. Satpayeva (Экономика: стратегия и практика, 2021)
In Kazakhstan, in recent years, there has been an intensification of urbanization processes due to the uncontrolled migration of rural population to cities. In this regard, there arise the number of problems related to ensuring the quality of life in cities.The purpose of this article is to assess the quality of urban space and its role in sustainable economic development on Almaty example. When assessing the quality of space in Almaty’s districts, there were calculated the groups of indicators that reflect the basic characteristics of a modern city: safety, comfort, ecology, diversity, modernity, business environment, quality of life, social development and human capital. Data from open sources were used: Department of statistics of Almaty, Committee on legal statistics and special accounts of the General prosecutor’s office of the Republic of Kazakhstan, Department of emergency situations of Almaty.The study concluded that the spatial development of Almaty is uneven. Four types of territories were identified in the city structure: the historic center, integrated with the adjoining business center; microdistricts of mass housing development (sleeping areas); old areas of low-rise buildings and private households; new annexed areas that are characterized by unregulated individual housing construction. As a result of the analysis, it was concluded that the quality of urban space is an important factor in the sustainable economic development of the city, in particular business.It was also concluded that it is necessary to develop a universal system of urban development indicators for use on an ongoing basis by representatives of business and the Akimat of Almaty in order to more fully identify the problems of urban space development, develop and implement strategic plans for the city’s development, as well as urban researchers.